THE PHYTOPLANKTON COMPOSITION of KADIKOY DAM LAKE (Keşan-EDİRNE) - Burak ÖTERLER (Trakya University Journal of Natural Sciences, 2015)
This study was carried out between June 2011 and May 2012 at different depths of three stations in Kadıköy Dam Lake in the Turkish Thrace. A total of seventyfour phytoplanktonic algal taxa belonging to Chlorophyta, Ochrophyta (Diatoms), Cyanobacteria, Euglenophyta, Charophyta, and Dinophyta were recorded during the study period. Members of Chlorophyta were found to constitute the dominant group in the lake. Some physical and chemical water quality parameters and trophic state of lake water were determined.